2022
DOI: 10.1111/een.13203
|View full text |Cite
|
Sign up to set email alerts
|

Experimental viral spillover can harmBombus terrestrisworkers under field conditions

Abstract: 1. Deformed wing virus (DWV), notorious for its virulence in the western honey bee (Apis mellifera) when vectored by the ectoparasitic mite Varroa destructor, is also widespread among wild bumble bee species, presumably through spillover from honey bees. Experimental studies on the virulence of DWV in Bombus spp. have provided equivocal results and have until now been confined to bumble bees under laboratory conditions.2. Here, we inoculated commercially reared Bombus terrestris workers with DWV-A through feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…In support of this view, when inoculated orally, a likely more natural mode of infection of bumblebees in the field [ 9 , 18 ], we also found that B. terrestris shed less DWV in faeces than did A. mellifera . Our data on viral shedding, along with the overall lower total DWV titres accumulating in adult B. terrestris compared to A. mellifera [ 28 , 29 ] and the lower infection rate observed after an oral challenge [ 27 ], suggest that B. terrestris constitutes a less suitable host for DWV-B than A. mellifera . Thus, DWV’s epidemiology in multi-species communities of bees is likely driven primarily by spillover from A. mellifera [ 10 , 11 , 12 ], the presumed reservoir host of this virus, rather than onward transmission from infected B. terrestris .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In support of this view, when inoculated orally, a likely more natural mode of infection of bumblebees in the field [ 9 , 18 ], we also found that B. terrestris shed less DWV in faeces than did A. mellifera . Our data on viral shedding, along with the overall lower total DWV titres accumulating in adult B. terrestris compared to A. mellifera [ 28 , 29 ] and the lower infection rate observed after an oral challenge [ 27 ], suggest that B. terrestris constitutes a less suitable host for DWV-B than A. mellifera . Thus, DWV’s epidemiology in multi-species communities of bees is likely driven primarily by spillover from A. mellifera [ 10 , 11 , 12 ], the presumed reservoir host of this virus, rather than onward transmission from infected B. terrestris .…”
Section: Discussionmentioning
confidence: 98%
“…In comparison, DWV has been shown to replicate in various tissue types of A. mellifera [42][43][44]. Furthermore, even though B. terrestris is known to support replication of DWV, shown by increasing virus titres after experimental infection [27][28][29]31], the low virus shedding we observed here in infected B. terrestris might additionally indicate a lack of molecular compatibility between DWV and B. terrestris, e.g., that the needed enzymes for virus release from the host cell are insufficient. For example, avian influenza virus spilling over to humans is often characterised by a viral neuraminidase that is insufficient to cleave the viral progeny from human host proteins, thus hindering effective cell release of new virions and viral spread despite virus replication [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few experiments have addressed the incidence of disease in DWV-infected bumble bees, but DWV has been shown to increase mortality in experimentally infected individuals both alone and with co-infection with the protozoan Apicystis bombi (Fürst et al 2014;Graystock et al 2016). Although a laboratory study considering the efficacy of proposed natural transmission routes suggested that transmission in the wild may be limited (Gusachenko et al 2020;Streicher et al 2023), research has demonstrated spillover from honey bees to bumble bees (Tehel et al 2022) and a potential introduction with non-native bumble bees (Arbetman et al 2013). The closely related Varroa destructor viruses (VDVs) and kakugo virus (KV) are considered by some to be variants of a DWV species complex (McMahon et al 2015).…”
Section: Virusesmentioning
confidence: 99%